Strategi Pengembangan Model Bisnis Teh Gaharu CV.Barokah Access, Sambas, Kalimantan Barat - Lukito Hasta Pratopo; Ahmad Thoriq (Fakultas Pertanian, Universitas Timor, 2020)
Agarwood leaves contain antioxidant compounds so that the potential as a raw material in making tea. One company that produces agarwood leaf tea is CV Barokah Access, Sambas, West Kalimantan, but in business development there are still many obstacles. This study aims to obtain alternative business development strategies through the Business Model Canvas and SWOT approaches. Data collected through observation and interviews, which are then processed using qualitative methods in the form of data reduction, data presentation and drawing conclusions. After conducting research, a strategy was produced for CV Barokah Access in developing the agarwood leaf tea business, namely: market development, product packaging improvement, strengthening partnership networks, increasing the number of employees, increasing human resource capacity, increasing business capital, and managing several business licenses.